2014
DOI: 10.1088/0264-9381/31/9/095004
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Cartan gravity with dynamical symmetry breaking

Abstract: It has been known for some time that General Relativity can be regarded as a Yang-Mills-type gauge theory in a symmetry broken phase. In this picture the gravity sector is described by an SO(1, 4) or SO(2, 3) gauge field A a bµ and Higgs field V a which acts to break the symmetry down to that of the Lorentz group SO(1, 3). This symmetry breaking mirrors that of electroweak theory. However, a notable difference is that while the Higgs field Φ of electroweak theory is taken as a genuine dynamical field satisfyin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 52 publications
1
31
0
Order By: Relevance
“…By recasting the equation for V 2 into a second order form we see that a viscous term appears and this suggests that the constancy of V 2 is caused by 'friction' causing the velocity |dV 2 /dτ | to decrease. Note that this mechanism is entirely distinct from the mechanism discovered in [41] wherein it was found that certain combinations of {ai, bi, ci} terms in the action were equivalent to a scalar-tensor theory equipped with a potential with stable minimum at non-zero V 2 . We leave it for future investigations to determine whether the former, new symmetry breaking mechanism also works outside the cosmological framework developed in this paper.…”
Section: Discussionmentioning
confidence: 78%
“…By recasting the equation for V 2 into a second order form we see that a viscous term appears and this suggests that the constancy of V 2 is caused by 'friction' causing the velocity |dV 2 /dτ | to decrease. Note that this mechanism is entirely distinct from the mechanism discovered in [41] wherein it was found that certain combinations of {ai, bi, ci} terms in the action were equivalent to a scalar-tensor theory equipped with a potential with stable minimum at non-zero V 2 . We leave it for future investigations to determine whether the former, new symmetry breaking mechanism also works outside the cosmological framework developed in this paper.…”
Section: Discussionmentioning
confidence: 78%
“…Other papers on extended MacDowell-Mansouri formalism include: An interesting paper [129] studying Stelle-West-type actions with a potential term for the compensator field instead of the Lagrange multiplier term. It is shown that the result is a variant of scalar-tensor theory of gravity.…”
Section: Macdowell-mansouri Type Unificationmentioning
confidence: 99%
“…The complication introduced by the a 1 and a 3 terms (only if a 3 depends on φ 2 ) is that spacetime gradients of φ can also couple to derivatives of C IJ in the C IJ equation of motion, hence in this case C IJ cannot generally be solved for algebraically in terms of e I and φ (and derivatives thereof) and hence eliminated from the variational principle. Specifically, such terms are [11]:…”
Section: Propagating Torsionmentioning
confidence: 99%